Down syndrome and outcomes in critically ill pediatric patients - Tantaleán Da Fieno, José; León Paredes, Rosa; Palomo Luck, Patricia; Del Águila Villar, Carlos; Rizo Patrón, Emiliana (Frontiers in Pediatrics, 2025)
IntroductionInformation regarding children with Down syndrome (DS) in the Pediatric Intensive Care Unit (PICU) is limited and conflicting. We aimed to investigate the association between DS and clinical outcomes in pediatric patients admitted to the PICU at the Instituto Nacional de Salud del Niño (National Institute for Child Health, INSN for the acronym in Spanish) and to assess nutritional status within the study cohort.MethodsThis study involved the secondary analysis of a database. We included patients consecutively admitted to INSN, a tertiary care children's hospital in Lima, Peru. We collected demographic data, clinical characteristics, and nutritional status using standardized tables. The outcomes assessed included mortality, length of stay, duration of mechanical ventilation (DMV), ventilator-free days (VFD), and healthcare-associated infections (HAI). We applied Cox regression and Poisson regression analyses to explore the relationship between Down syndrome and clinical outcomes, providing both crude and adjusted results.ResultsA total of 525 children (average age 71.3 months, range 1–218 months) were analyzed. Children with DS were younger and had a higher prevalence of comorbidities, congenital heart disease, and underweight. Both crude bivariate and multivariate analyses demonstrated that children with DS had higher mortality rates, increased frequency of HAIs, longer DMV, longer PICU stay, and fewer VFD. Adjusted multivariate analysis revealed that children with DS had a significantly higher risk of developing HAIs (RR 2.95; 95% CI 1.10, 7.87) and longer DMV (RR 1.43; 95% CI 1.24, 1.65). Among the 525 children, underweight was associated with increased risk of mechanical ventilation (MV) use and longer DMV.DiscussionCritically ill children with DS are at increased risk of developing HAIs and longer DMV. In all 525 children, underweight is associated with higher risk of MV use and longer duration of MV.